Use of a modified Yo-Yo intermittent endurance level 2 test for evaluation of field soccer referees - Paes, M. R.; Fernandez, R. (Sport Sciences for Health, 2024)
Background Since 1989, FIFA has used a battery of physical tests to evaluate the fitness levels of soccer referees. However, to date, there is no consensus, and the specificity, reliability, and validity of these tests remain a matter of debate.